Fondasi Etis Ekonomi Pada Masa Rasulullah (Sebuah Kajian Historis-Normatif) - Ayief Fathurrahman (JES (Jurnal Ekonomi Syariah), 2018)
It is certainly undeniable that in Islam the source of ethics in the line of life is the Prophet Muhammad, including ethics of economic activity. Islam which was the beginning of its glory in the time of the Prophet Muhammad also had the concept of an economic system that should be used as a lesson and reference materials. Therefore, this paper will explain the economic activities of the pre-Islamic Arabs as a comparison with the economic activities that have been straightened out by the Messenger of Allah, which includes an initial strategy to build the economy of Medina, fiscal policy, so as to achieve social equity. The result of research shows that the economic activity of the pre-Islamic Arabs had become the World Trade Center, both in the southern part of the Arabian Peninsula which was managed by the Saba kingdom and the Himyar government with the dominant agricultural sector having fertile land. It is also supported by the presence of the Maarib giant dam. In the northern part of the Arab, Hijaz (Makkah) which was influenced by outsiders such as Persia and Rome, with the most prominent trade sector, because the territory was barren and arid, but the geographical location was strategic as a place for the caravans to stop. The economic characteristics of the Prophet's time were social-religious which emphasized cooperative work participation applied to Muhajirin and Ansar which led to increased income distribution and welfare. This is where the concept of economic democracy of the Prophet is seen which does not have to be interpreted as the enactment of the principle of equal treatment, because according to the Prophet the Have Not needs to get a partial treatment. In principle, the Messenger of Allah highly prioritizes the achievement of mutual welfare. Keywords: Economic Ethical Foundation, Historical-Normative Study, Rasulullah Era